A substructured FE/XFE method for stress intensity factors computation in an industrial structure - Wyart, Eric; Coulon, Danielle; Martiny, Philippe; Pardoen, Thomas; Remacle, Jean-François; Lani, Frédéric (European Journal of Computational Mechanics, 2007)
The introduction of the eXtended Finite Element Method (X-FEM) into a commercial Finite Element (FE) software was achieved through a substructuring method. For fracture mechanics problems, the domain is decomposed into cracked and safe subdomains which are solved by the XFE-code and the FE-software, respectively. The interface problem is solved using a FETI solver. The new approach is compared with a classical FE-approach in the case of a planar crack in a compressor drum of a turbofan engine.